Pengaruh Kompensasi Terhadap Kinerja Karyawan Bagian Produksi Pada Perusahaan PT. Semen Tonasa II Dan III Kabupaten Pangkep - Alex Sander; Rina Rina; Monalisa Monalisa (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2024)
This research aims to determine the effect of compensation on the performance of employees in the production department at PT. Semen Tonasa II and III Pangkep Regency. The method used in this research is a quantitative method with the number of respondents being 51 employees who were used as samples using a sampling technique, namely using Solvin samples. The analysis used in this research is a simple linear regression test. The results of simultaneous testing of the education level variable have a positive and significant effect on the work productivity variable as proven based on the results of the simultaneous test with a significance value of f<α (0.000<0.05). The partial test results of the compensation variable have a positive and significant effect on employee performance variables with a significance value of f<α (0.000<0.05).